Advances in seed yam propagation methods in Nigeria - Ikeorgu, J.G.; Mazza, M.A.; Okonkwo, C.; Kikuno, H. (International Society for Tropical Root Crops, 2012)
Scarcity and/or high cost of healthy seed yams are the greatest constraints in yam production in Nigeria and probably across the West African Yam belt. Scientists at the National Root Crops Research Umudike developed the yam minisett technique of seed yam production in 1982 but nearly three decades after, the adoption rate of this technology is still below 40%. Concerned about this development, the World Bank mission to Nigeria supervising the National Agricultural Research Projects (NARP) in 1997 wondered why Nigeria could not develop effective systems that would ensure rapid adoption of this proven technology or develop complementary seed yam propagation technologies that would enable farmers to gain access to newly released, high yielding yam varieties soon after release. This paper, therefore, discusses the progress made so far in promoting the yam minisett technique and three other technologies (minituber, vine-cuttings and peelsett) developed to complement the yam minisett technique.